Manajemen Waktu Untuk Siswa & Pekerja Pemula - Eka Sri Rahayu Noviani; Fahmi Susanti; Muhammad Adit Tyo Ramadhan; Christian Lee Lumban R (Advances In Education Journal, 2026)
Time management skills are important abilities for students and novice workers in facing academic demands as well as the world of work. However, many individuals still experience difficulties in managing their time effectively, such as procrastination, lack of prioritization, and poorly structured activity management. This program aims to provide basic time management training to students through interactive methods such as discussions, simulations, and hands-on practice. The results of the activities show an increase in participants' understanding of how to set priorities, create schedules, and improve productivity. Participants also show behavioral changes, becoming more disciplined and organized in completing tasks.